Electron temperature and heat load measurements in the COMPASS divertor using the new system of probes. (3rd August 2017) - Adamek, J.; Seidl, J.; Horacek, J.; Komm, M.; Eich, T.; Panek, R.; Cavalier, J.; Devitre, A.; Peterka, M.; Vondracek, P.; Stöckel, J.; Sestak, D.; et al.
Abstract: A new system of probes was recently installed in the divertor of tokamak COMPASS in order to investigate the ELM energy density with high spatial and temporal resolution. The new system consists of two arrays of rooftop-shaped Langmuir probes (LPs) used to measure the floating potential or the ion saturation current density and one array of Ball-pen probes (BPPs) used to measure the plasma potential with a spatial resolution of ~3.5 mm. The combination of floating BPPs and LPs yields the electron temperature with microsecond temporal resolution. We report on the design of the new divertor probe arrays and first results of electron temperature profile measurements in ELMy H-mode and L-mode. We also present comparative measurements of the parallel heat flux using the new probe arrays and fast infrared termography (IR) data during L-mode with excellent agreement between both techniques using a heat power transmission coefficient γ   =  7. The ELM energy density ε ∥ was measured during a set of NBI assisted ELMy H-mode discharges. The peak values of ε ∥ were compared with those predicted by model and with experimental data from JET, AUG and MAST with a good agreement.